Effect of germination on total dietary fiber and total sugar in selected legumes - Megat, R. M. R.; Azlan, Azrina; Mohd Esa, Norhaizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Legume is a plant in the family of Fabaceae (or Leguminosae) that is cultivated and consumed throughout the world. Legume’s role in human health appears to be limited because of several limiting factors such as low protein and starch digestibility, poor mineral bioavailability and high antinutritional factors. Germination is defined as a process that occurs during seed growth that starts with uptake of water until the emergence of radicle through the surrounding structure. It has been suggested that germination is a cheaper and more effective technology that can improve the quality of legumes by increasing their nutritional value. This study was conducted to compare changes in dietary fibre and total sugar compositions after germination process in kidney, mung, soy beans and peanuts. Total dietary fibre was found to be significantly increased (p<0.05) in all germinated samples, with significant increased (p<0.05) of soluble and insoluble dietary fibres. For total sugar content, germination increased the level of total sugars. Glucose was the highest available sugar in samples that increased after germination while arabinose was second available sugar that increased in germinated legumes except kidney beans. Overall, germination has improved nutritional properties of legumes in terms of dietary fibre and total sugar content but the changes are influenced by the type of legumes.